2021
DOI: 10.3390/encyclopedia1010020
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Integrity and COVID-19

Abstract: Tissue integrity depends on biological tissue stiffness. Tissue integrity can protect both against age-related diseases and against severity of COVID-19. The disruption of tight junctions and increase of tissue permeability with advancing age can be related with age-related diseases as well as with age-dependent COVID-19. Release of tightly bound water from collagen fibrils leads to the increase of extracellular matrix stiffness and to the associated with matrix stiffness increased tissue permeability. The lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 114 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…Dehydration also results in enhanced tissue stiffness and triggers NF-κB activation [ 11 ]. Hydration at biointerfaces prevents platelet adhesion and thrombus formation [ 3 ].…”
Section: Possible Causes Of Covid-19 Severitymentioning
confidence: 99%
See 3 more Smart Citations
“…Dehydration also results in enhanced tissue stiffness and triggers NF-κB activation [ 11 ]. Hydration at biointerfaces prevents platelet adhesion and thrombus formation [ 3 ].…”
Section: Possible Causes Of Covid-19 Severitymentioning
confidence: 99%
“…It was also observed that atherosclerosis, diabetes, and obesity are associated with the stiffening of blood vessel walls and the recruitment of inflammatory leukocytes out of the bloodstream into tissues. It has been demonstrated that the decrease of water molecules binding energy with biological macromolecules leads to the release of tightly bound water and the increase of ECM stiffness with the disruption of tissue integrity [ 3 ].…”
Section: Possible Causes Of Covid-19 Severitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this ongoing COVID-19, TE has an important role in the application of the Bioscaffold matrix, the treatment of COVID-19 infection, the healthy functioning of the body and the examination of healing mechanisms. In the future, TE will play an important role in saving the life of a COVID-19 patient (Malavazos et al, 2020;Tatara, 2020;Bailey et al, 2021;Dorward et al, 2021;Kerch, 2021).…”
Section: Tissue Engineering and Covid-19mentioning
confidence: 99%